EXPEDIENCY OF TEMPORAL TRACHEOSTOMY IN PATIENTS SURGICALLY TREATED FOR DISCONTINUITY OF THE MANDIBULAR ARCH - D. V. Sikorsky; S. O. Podvyaznikov; A. A. Chernyavsky; A. N. Volodin (Опухоли головы и шеи)
The paper analyzes clinical observations of 40 patients with locally advanced and recurrent oropharyngeal cancer, who underwent multicomponent surgery with simultaneous removal of a primary tumor and cervical lymph outflow tracts, which was accompanied by discontinuity of the mandibular arch with concurrent tracheostomy.